THE USE OF ENGLISH IN ONLINE ARTICLES PROMOTING SOUTH KALIMANTAN - Ninuk Krismanti; Agustina Lestary; Imam Hendra Saputra (Universitas Lambung Mangkurat, 2018)
Abstract: When compared to popular destinations like Bali or Jogjakarta, the number of tourists visiting South Kalimantan is of course lower. It takes sustainable efforts for South Kalimantan tourism board and related parties to promote this province tourism. Online English articles promoting South Kalimantan are sadly not that many in number. When English articles describing about tourist destinations and hospitality of Banjarese people are hardly found online, at least the articles are well written in order to sell the tourism of this province better. However, language barrier may cause the writers of the articles to use English incorrectly. This study is set to contribute to the promotion of South Kalimantan tourism in terms of foreign language usage. The study is descriptive research because its main objectives are to describe how English is used in articles promoting South Kalimantan and to suggest possible improvements for the misuse of English found in the articles. This research is conducted for three months, December 2017 – February 2018. The location of the research is Banjarmasin. The data of this research are collected from six websites promoting South Kalimantan. After the articles becoming the data of this study are collected, they are read carefully in order to determine the accuracy of the English used in the articles and to find the language phenomena being questioned in this research. After making the decision on the accuracy of English usage in the articles, the researchers then focus to find the misuses of English in the investigated articles. The results of the study are useful to review how English is used in online articles promoting this province. The conclusions drawn for this study are (1) the English used in online articles promoting South Kalimantan are generally accurate though several misuses of the language are still found, (2) syntactic problems in the articles do not disturb of the flow of the stories being told. Thus, the writers of the articles have been successful in promoting South Kalimantan through their writings, (3) Semantic problems in the articles are not that many though improvements are still neededrole, and how it promotes active students’ interaction.